2004
DOI: 10.1590/s0004-282x2004000600025
|View full text |Cite
|
Sign up to set email alerts
|

Conhecimentos e atitudes sobre epilepsia entre universitários da área da saúde

Abstract: RESUMO -Vários estudos em diversos paises mostram em relação à epilepsia a falta de conhecimentos, os preconceitos e as repercussões negativas para os pacientes. Avaliamos os conhecimentos e atitudes de universitários da área da saúde no início e ao final dos cursos. Foram aplicados questionários contendo 15 questões em relação à epilepsia a 564 universitários (290 do primeiro e 274 do último ano) de cinco cursos (ciências farmacêuticas, fisioterapia, medicina, nutrição e terapia ocupacional). Os estudantes de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
5
0
2
Order By: Relevance
“…In the present survey, the degree of familiarity with epilepsy indicated by university students in the health area and the levels of adequate responses given to the questionnaire in the fi rst phase of the study, were similar to those found in a similar survey carried out previously in the same university 17 , confi rming a basic lack of knowledge about various aspects of epilepsy. The proposal for a workshop on the theme of epilepsy stimulated interest amongst students in various courses in the health area, resulting in signifi cant participation.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In the present survey, the degree of familiarity with epilepsy indicated by university students in the health area and the levels of adequate responses given to the questionnaire in the fi rst phase of the study, were similar to those found in a similar survey carried out previously in the same university 17 , confi rming a basic lack of knowledge about various aspects of epilepsy. The proposal for a workshop on the theme of epilepsy stimulated interest amongst students in various courses in the health area, resulting in signifi cant participation.…”
Section: Discussionsupporting
confidence: 88%
“…Questionnaire -The questionnaire was based on items related to familiarity, knowledge, attitudes and care during an epileptic fi t, consisting of 15 questions already applied in the previous survey 17 , and, to a large extent, already applied in other surveys as well 3,8,19 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…De fato, os estudantes universitários representam um grupo da sociedade que detém conhecimento que contribuirá para o crescimento do país (HASSONA et al, 2014). Portanto, é importante que alunos do ensino superior, principalmente, os da área da saúde tenham um entendimento correto do que é epilepsia, já que serão profissionais importantes na disseminação de conhecimento para a sociedade (FONSECA et al, 2004). Sendo assim, a presente pesquisa teve por objetivo verificar o conhecimento sobre epilepsia de alunos da graduação dos cursos da Saúde da Universidade Federal de Alagoas.…”
Section: Introductionunclassified